Aspects of Social Sustainability in Planning and Renewal of Housing Estates - Skalicky, Vanja; Sitar, Metka (Journal for Geography, 2011)
The chapter highlights a few aspects of social sustainability issues concerning planning and renewal of housing estates, in Slovenia generally comprising of multi-family residential buildings and public buildings, open public space and parking areas. As a phenomenon, the characteristic influence of Scandinavian models, especially Swedish that have radically changed urban design and architecture practice in Slovenia are presented and investigated in the context of historical perspective, with emphasis on the organization and planning on the post-war housing estates development in Maribor. Currently, in order to raise the housing quality, the modern urban renewal methods expose the open public space planning as the most decisive factor.